The Saving Behavior of Public Vocational High School Students of Business and Management Program in Semarang - Chalimah, Siti Nor; Martono, S.; Khafid, Muhammad (Journal of Economic Education, 2019)
Saving behavior needs to be instilled in young children up to adulthood. The culture of saving that is instilled early on in children can give many benefits, form economical characters, discipline in spending money and prepare for the future. The purpose of this study was to analyze and find empirical proves of the role of parents, financial literacy, and self-control and future perceptions on students’ saving behavior as well as the influence of parents’ role financial literacy, self-control and future perceptions on students’ saving behavior. The type of research is quantitative with the correlational approach. The research technique used was proportional stratified random sampling with samples of 247 students. The data analysis technique used path analysis. The results of the study indicated that the role of parents, financial literacy, self-control, and future perceptions affect saving behavior. Parents' role affects saving behavior through financial literacy, self-control and future perceptions as mediating variables.